Criminal Responsibility For Perpetrators Of Fraud By Means Of Hypnosis - Agustian Fery Fernando Sitanggang; T. Riza. Zarzani (ASIAN PUBLISHER, 2023)
This study aims to analyze the criminal liability of perpetrators of fraud by means of hypnosis. This research is a normative literature research as a legal material collection technique which is then analyzed qualitatively and presented descriptively. As for the results of this study, taking other people's goods by means of hypnosis can be categorized as a criminal act of fraud because of the fulfillment of one of the elements of the offense of fraud, namely the element of deception, which is an act of action carried out in such a way that the act creates trust or confidence in the truth of something to another person where it can influence people to move other people to hand over something to him to be his goal in owning other people's goods. And if done consciously and there are consequences caused by the act. Next, the theory of criminal responsibility that is appropriate to be applied in this case is the doctrine of the essential elements of crime, namely actus reus (physical element) mens rea (mental element), namely the state of mind. The dualism school, on the other hand, states that only the actus reus is an element of an offense, while the mens rea includes the responsibility of the maker. The crime of fraud with hypnosis in its enforcement efforts still has many obstacles, including people who are victims who are reluctant to report, legal substance factors, law enforcement factors, supporting facilities and facilities for crime prevention. And the factor of public awareness of the law.